2021
DOI: 10.1364/oe.434772
|View full text |Cite
|
Sign up to set email alerts
|

High-speed temporal and spatial beam-shaping combining active and passive elements

Abstract: Temporal and spatial shaping of laser beams is common in laser micromachining applications to improve quality and throughput. However, dynamic beam shaping (DBS) of ultrashort, high-power pulses at rates of hundreds of kHz has been challenging. Achieving this allows for full synchronization of the beam shape with high repetition rates, high-power lasers with zero delay time. Such speeds must manipulate the beam shape at a rate that matches the nanosecond to microsecond process dynamics present in laser ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[113][114][115][116] Additionally, the combination of spatial and temporal beam shaping could be leveraged to achieve dynamic temporal beam shaping for specific applications. [117] While spatial and temporal beam shaping offer significant benefits, it is important to note that this review focuses solely on continuous wave (CW) laser beam shaping. Therefore, the literature pertaining to temporal beam shaping applications in L-PBF will not be covered here.…”
Section: Temporal Beam Shapingmentioning
confidence: 99%
“…[113][114][115][116] Additionally, the combination of spatial and temporal beam shaping could be leveraged to achieve dynamic temporal beam shaping for specific applications. [117] While spatial and temporal beam shaping offer significant benefits, it is important to note that this review focuses solely on continuous wave (CW) laser beam shaping. Therefore, the literature pertaining to temporal beam shaping applications in L-PBF will not be covered here.…”
Section: Temporal Beam Shapingmentioning
confidence: 99%
“…To overcome the limitations concerning the critical energy fluence on spatial light modulators (SLMs), which causes phase distortions or even material damage, power splitting by using multiple devices was demonstrated [16]. Recently, it was shown that the combination of multi-aperture diffractive-optical elements and acousto-optic deflectors enables one to reach high temporal flexibility with repetition rates up to 330 kHz for conventional beam profiles and shaping on nanosecond scale [17]. Such systems are of particular interest for high-speed and high-power micromachining.…”
Section: Introductionmentioning
confidence: 99%